2015
DOI: 10.1016/j.afju.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ureteroscopy for the management of distal ureteric calculi: 5-years’ experience

Abstract: Objective: To review our 5 years' experience with ureteroscopy treatment of distal ureteric calculi. Patients and methods: We reviewed the medical records of 136 patients who underwent ureteroscopic procedures for the treatment of distal ureteric calculi from February 2007 to October 2012. Patient and stone characteristics, treatment modality and outcome were assessed. Procedure's duration, status "stone free" and hospital stay were also evaluated. The mean clinical and radiological follow-up period was 31.8 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…16 In Weimin Yu, Fan Cheng et al 2014 retrograde ureteroscopic treatment for upper ureteral stones: A 5-Year Retrospective Study Overall, the stone-free rate was 90.4%, the mean operative duration was 41.2 ± 10.7 minutes, in our study the overall success rate was 93.7% and mean operative time was 26.1 minutes. 17 Ureteral stenting following uncomplicated URS is optional: several randomized prospective studies published since the 1997 AUA guideline document has demonstrated that routine stenting after uncomplicated URS may not be necessary.…”
Section: Success Ratementioning
confidence: 64%
“…16 In Weimin Yu, Fan Cheng et al 2014 retrograde ureteroscopic treatment for upper ureteral stones: A 5-Year Retrospective Study Overall, the stone-free rate was 90.4%, the mean operative duration was 41.2 ± 10.7 minutes, in our study the overall success rate was 93.7% and mean operative time was 26.1 minutes. 17 Ureteral stenting following uncomplicated URS is optional: several randomized prospective studies published since the 1997 AUA guideline document has demonstrated that routine stenting after uncomplicated URS may not be necessary.…”
Section: Success Ratementioning
confidence: 64%
“…The choice of management depends on the stone's site and characteristics, preference of patient and associated cost. 8 These techniques include ureteroscopy 9 , extracorporeal shockwave lithotripsy (ESWL) and laparoscopic ureterolithotomy. 8,10,11 Among them ureterorenoscope 9 by using Lithoclast is one of the leading management solution for the removal of ureteric stone removal.…”
Section: Introductionmentioning
confidence: 99%
“…8 These techniques include ureteroscopy 9 , extracorporeal shockwave lithotripsy (ESWL) and laparoscopic ureterolithotomy. 8,10,11 Among them ureterorenoscope 9 by using Lithoclast is one of the leading management solution for the removal of ureteric stone removal. 8,12,13 The objective of this research was to decide the adequacy of ureterorenoscope by utilizing lithoclast for ureteric stone clearance.…”
Section: Introductionmentioning
confidence: 99%
“…3 With the advancement of ureteroscopic technologies, treatments for the removal of ureteral calculi have shown decreased procedural invasiveness with high success rates and limited morbidity. 4 In their paper, de la Rosette et al analyzed 11,885 ureteral calculi patients treated with ureteroscopy and revealed that the stone-free rate and postoperative complication rate were 85.6% and 3.5%, respectively, 5 suggesting that ureteroscopy can be used in patients with larger and more complicated stones, as well as elderly patients with significant comorbidities. 4 However, the incidence of severe complications is still high after ureteroscopy treatment, including febrile urinary tract infection (UTI).…”
Section: Introductionmentioning
confidence: 99%
“…4 In their paper, de la Rosette et al analyzed 11,885 ureteral calculi patients treated with ureteroscopy and revealed that the stone-free rate and postoperative complication rate were 85.6% and 3.5%, respectively, 5 suggesting that ureteroscopy can be used in patients with larger and more complicated stones, as well as elderly patients with significant comorbidities. 4 However, the incidence of severe complications is still high after ureteroscopy treatment, including febrile urinary tract infection (UTI). Therefore, it is urgent to explore factors that may affect the postoperative occurrence of febrile UTI to provide a new therapeutic target for the treatment of ureteral calculi.…”
Section: Introductionmentioning
confidence: 99%